Pengaruh Variasi Waktu Annealing Terhadap Struktur Mikro dan Sifat Mekanik Baja Paduan Fe-Mn-Al-C - Setyo Pamuji, Didit; Sutrisna; Yohanes Agus Jayatun (ReTII, 2023)
Fe-Mn-Al-C alloy steel is a new austenitic stainless steel candidate alloy, where Al and Mn elements replace Cr and Ni elements. After casting alloy steel Fe-14.8 Mn-11.9 Al-0.7 C turned out to have a hardness of up to 42 HRC and difficult to machining. This study specifically aims to further investigate the effect of spheroidizing annealing process on alloy steel Fe-14.8 Mn-11.9 Al-0.7 C by varying the annealing time to increase tensile strength, microstructure stability, and decrease the hardness value. Ingot sheets are formed into several specimens and then annealed at a temperature of 1100 Â° with time variations of 45, 60, and 90 minutes. The specimens were tested for chemical composition, microstructure analysis, and mechanical properties. In the microstructure of raw materials obtained Ferrite and austenite phases, based on the results of microstructure photos at the time variations found no new phase and no significant difference, visible ferrite structure becomes larger / more elongated and austenite structure is shrinking. Hardness test results using the highest Vickers method in raw materials amounted to 463.6 kg / mm2 after the annealing process hardness value decreased but not significantly, because after peroses annealing ferrite structure obtained that looks bigger. The results of tensile strength testing of raw materials amounted to 343.58 MPa and obtained the highest stress in the variation time 45 minutes of 422.18 Mpa, or increased by 22.8%.